Where are You Now? - Clark, Mary Higgins (New York Pocket Books, 2009)
As Carolyn MacKenzie unravels the mystery behind her brother's disappearance ten years ago, she confronts someone close to her that is equally determined to keep his whereabouts secret at any cost.
Includes an excerpt from "Just take my Heart" (p. [341-353]).
Keywords: Missing persons -- Brothers and sisters -- Missing persons--Investigation